User Interface Design of Mykonter Mobile Application Using User Centered Design Method on Konter Sam Cell - Beby Ayu Astina; Qadhli Jafar Adrian; Donaya Pasha (Electronic Integrated Computer Algorithm Journal, 2024)
Sam Cell is a counter business where sales are still done manually without the help of technology. Sam Cell's sales only cover the area around the counter and are not yet widespread in all regions, so income is still relatively small compared to other counter businesses. Sam Cell also doesn't have a good promotional system to increase sales. So this research has sales innovation through application design. Therefore, to achieve this goal, the user centered design method was chosen in designing the Mykonter application which focuses on user convenience (usability) and satisfaction (satisfaction) with the application design. The user centered design method consists of 4 iterative stages which can be used to strengthen innovation, solve a problem and help understand user needs so as to provide the right solution. The results obtained from user validation when using the Prototype are the conclusion that the application design has met the benchmark criteria, by obtaining a user satisfaction level of 53.5 points, where these points have met the criteria rules for measuring the System Usability Scale so that this application design can be developed by the development team to serve as a basis for building a Mykonter application design.